Factors of academic stress: Do they impact English academic performance? - Erlinda D. Tibus; Sybill Krizzia G. Ledesma (Institute of Advanced Engineering and Science, 2021)
This study investigated the college students’ level of academic performance and determined the impact of academic stress on their English academic performance. This employed a descriptive-exploratory research design with Exploratory Factor Analysis (EFA) and correlation analysis (Pearson r) as main analyses using statistical software. The result suggested that the students (N=250) have a moderate level of stress. Likewise, seven factors were generated through EFA but were reduced to four factors using parallel analysis, the factors are perceived personal stress, classroom stress, performance stress, and time management stress. In the correlation analysis, it was found out that perceived personal stress, classroom stress, and performance stress are significantly correlated except for time management stress. Moreover, these factors were found to have no significant relationship with the English grades of the students. With this result, it is concluded that despite having a moderate level of academic stress, students were able to manage them by using a plethora of coping mechanisms available. The institutions should offer prevention and intervention services that directly address the academic stress of the students to ensure academic success.